The relationship between urban and rural health insurance and the self-rated health of migrant workers in Southwest China - Dingying Fu; Li Liu; Xuewen Zhang; Chuan Yu; Huiqiang Luo; Ningxiu Li (BMC, 2021)
Abstract Background Following health insurance reforms, China's health care system has made great progress. However, there are still huge differences between the urban and rural health insurance systems. For rural-to-urban migrant workers, there may be differences in the use of urban and rural health insurance to improve their health status. This study aimed to determine whether any disparities exist in the relationship between urban and rural health insurance and the self-rated health (SRH) of migrant workers in Southwest China from the perspective of urban and rural segmentation. Methods Using cross-sectional survey data on Southwest China in 2016, a representative data sample drawn from 8507 migrant workers was analysed. An ordinary least squares (OLS) model and instrumental variable (IV) estimation were used to analyse the relationship between urban and rural health insurance and the SRH of migrant workers. Results Using the IV method to control the endogeneity problems associated with health insurance, this study found that there are differences in the relationship between urban and rural health insurance and the SRH of migrant workers. Urban health insurance is associated with significant improvements in the SRH of migrant workers. Compared with the NRCMS, participating in urban health insurance, including urban employee basic medical insurance (UEBMI) and urban resident basic medical insurance (URBMI), increases the likelihood of migrant workers having better SRH. Conclusions There are disparities in the relationship between urban and rural health insurance and the SRH of migrant workers in China. Compared to rural health insurance, urban health insurance has a more positive correlation with the health of migrant workers. Our study shows that it is necessary to integrate urban and rural health insurance to promote social equity.